La expresión emocional en alumnos de altas capacidades - Caño Sánchez, Maximiano Del; Palazuelo Martínez, Mª Marcela; Marugán de Miguelsanz, Monserrat; Frutos Diéguez, Carlos De; Quintero González, Mario (FAISCA: Journal of High Abilities, 2011)
This paper aims at analyzing how a group of gifted students express their emotions as well as finding any significant differences in this variable with regard to gender and chronological age. A sample of 41 students has been selected (19 girls and 22 boys) from several schools in the city of Valladolid and its surroundings. The students are from 6 to 12 years old and take part in an extracurricular enrichment program. Diverse and original productions made by the students and specifically designed for this research have been analyzed in order to come to the definitive findings
Keywords: Gifted students; Emotions; Emotional response; Primary Education; Values